Neutrophil and lymphocyte counts are associated with different immunopathological mechanisms in systemic lupus erythematosus. Issue 1 (21st May 2020) - Han, Bobby Kwanghoon; Wysham, Katherine D; Cain, Kevin C; Tyden, Helena; Bengtsson, Anders A; Lood, Christian
Abstract : Objective: Neutrophils contribute to the SLE pathogenesis. Neutrophil to lymphocyte ratio (NLR) is reported to correlate with disease activity in SLE. The aim of the study was to evaluate whether NLR reflects underlying immunopathogenic activity in SLE, as well as to determine the contribution of each component of NLR, neutrophil and lymphocyte count. Methods: Data were obtained from a cohort of patients with SLE (n=141) recruited at Lund University, Sweden. NLR levels were compared between patients with SLE and healthy controls (n=79). The relationship between NLR and clinical and immunological markers was examined using Mann-Whitney U test and logistic regression analysis. High NLR was defined as above the 90th percentile of healthy individuals. Results: Patients with SLE had elevated neutrophil count (p=0.04) and reduced lymphocyte count (p<0.0001), resulting in elevated NLR as compared with healthy controls (p<0.0001). Patients with high NLR had more active disease, and were more frequently on prednisone use and immunosuppressive medicines. High NLR was associated with immune complex (IC)-driven disease with presence of antidouble-stranded DNA antibodies (p=0.006), circulating ICs (p=0.02) and type I interferon (IFN) activity (p=0.009). Further, high NLR was associated with neutrophil abnormalities, including enrichment for low-density granulocytes (LDGs) (p=0.001), and increased levels of the serum neutrophil activation marker, calprotectin (p=0.02). Assessing the individual components within NLR, that is, neutrophil and lymphocyte count, high neutrophil count was associated with neutrophil activation markers (p<0.0001), whereas low lymphocyte count was associated with type I IFN activity and elevated numbers of LDGs (p=0.006 and p=0.001, respectively). Conclusions: NLR is elevated in patients with SLE as compared with healthy individuals, and is associated with key immunopathological events, including type I IFN activity and neutrophil activation. Neutrophil and lymphocyte count reflected different aspects of the pathogenesis of SLE. Further studies are needed to determine the causality of the associations.